Numerical simulation of solvent and water assisted electrical heating of oil sands including aquathermolysis and thermal cracking reactions. Issue 9 (10th May 2017) - Hassanzadeh, Hassan; Rabiei Faradonbeh, Moosa; Harding, Thomas
Abstract : Simulations of bitumen recovery using solvent‐ and water‐assisted electrical heating of oil sands are presented to evaluate the process and to study gas generation. Aquathermolysis and thermal cracking and dissolution of acid‐gases in water are included. Steam‐assisted gravity drainage (SAGD) is also simulated for comparison. Results show that gas generation negatively impacts SAGD. However, in electrical heating dissolution of gases into solvent weakens their negative impact. Results indicate that SAGD generates a larger gas volume than electrical heating. In both processes, methane is found to be the major species in the produced gas and H2 S concentration can reach high values. While the effect of acid–gas solubility in water on oil recovery is not evident its effect on generated gas volume is significant. Simulation results demonstrate that electrical heating is more energy efficient than SAGD. These results find application in design of experiments and pilot and field‐scale implementation of the process. © 2017 American Institute of Chemical Engineers AIChE J, 63: 4243–4258, 2017